2022
DOI: 10.1364/optica.455672
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal photonic crystals

Abstract: We study light propagation in spatiotemporal photonic crystals: dielectric media that vary periodically in both space and time. While photonic crystals (spatially periodic media) are well understood, the combination of periodic change in both time and space poses considerable challenges and requires new analysis methods. We find that the band structure of such systems contains energy gaps, momentum gaps, and mixed energy–momentum gaps in which both energy and momentum may attain complex values. We identify the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(29 citation statements)
references
References 38 publications
0
29
0
Order By: Relevance
“…Furthermore, it is shown that a metasurface-based PhTC can be excited externally by plane waves, amplifying both surface-bounded and free-space harmonics. The proposed metasurface platform can significantly simplify the construction and exploration of PhTCs, providing great convenience for probing the physics in PhTCs and photonic space-time crystals [28,29]. From the application point of view, the demonstrated metasurface PhTCs can become an important contribution to surface wave communications, serving as a "filling station" for surface-wave signals.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it is shown that a metasurface-based PhTC can be excited externally by plane waves, amplifying both surface-bounded and free-space harmonics. The proposed metasurface platform can significantly simplify the construction and exploration of PhTCs, providing great convenience for probing the physics in PhTCs and photonic space-time crystals [28,29]. From the application point of view, the demonstrated metasurface PhTCs can become an important contribution to surface wave communications, serving as a "filling station" for surface-wave signals.…”
Section: Discussionmentioning
confidence: 99%
“…The spatial variations can be along one, two, or three dimensions. Photonic crystal properties can even be variable with time (the co-called spatiotemporal photonic crystals [ 57 ]).…”
Section: Photonic Crystals Based On Nanomembranesmentioning
confidence: 99%
“…In wake of tremendous scientific and technological advancements in the last decade, photonic time crystals (PTCs) have been introduced as a distinct tool for light manipulation with unique features opening up new avenues in the domain of photonics. PTCs are systems where the refractive index (n) varies periodically with time [1,2], the study of which has brought light to many underlying features like temporal localization in between two PTCs with dissimilar topologies [3], localization of pulses and exponential decay in group velocity of a pulse in disordered PTCs [4], exceptional points in spatio-temporal crystals [5], and more with their intriguing physics. The concept of PTCs, so far, has been demonstrated in transmission lines for radio frequencies [6] and tremendous efforts are being put forward towards their realisation in optical regime using transparent conducting oxides (TCOs) [7].…”
mentioning
confidence: 99%